PENGARUH DISTRIBUTION INTENSITY, ADVERTISING, DAN SALES PROMOTION TERHADAP BRAND AWARENESS, DAN BRAND EQUITY PADA PRODUK SUNLIGHT DI SURABAYA - GUSTIAN, . (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
Research carried out aimed to determine the impact of distribution intensity, advertising, and sales promotion on brand awareness, and brand equity on Sunlight product in Surabaya. This research uses structural equation modeling (SEM) method. Sampling technique in this research is sampling purposive. This research uses sample of 150 respondents. Characteristics of the sample are people who know Sunlight product and advertisement. The results showed that distribution intensity has positive effect on brand awareness. Advertising has positive effect on brand awareness. Sales promotion has positive effect on brand awareness. Brand awareness has positive effect on brand equity.